Electronic structure modulation of CoSe2 nanowire arrays by tin doping toward efficient hydrogen evolution. (13th May 2021) - Liu, Caichi; Hu, Yongchuan; Liu, Fang; Liu, Hui; Xu, Xuewen; Xue, Yanming; Zhang, Jun; Li, Ying; Tang, Chengchun
Abstract: The development of highly active, durable and earth-abundant electrocatalysts toward hydrogen evolution reaction (HER) is of great significance for promoting hydrogen energy. As one of the most potential substitutes for Pt-based materials, pyrite cobalt selenide (CoSe2 ) still has shortcomings in terms of HER performance possibly due to its unfavorable hydrogen adsorption characteristics. Metal cation doping has been considered as one of the most available methods to modulate the electronic structure of electrocatalysts. Herein, non-transition metal tin (Sn) doped CoSe2 nanowire arrays grown on carbon cloth have been constructed and fabricated via a simple gas-phase selenization treatment of hydroxide precursor. The successful doping of Sn element into CoSe2 nanowires was confirmed by many experimental results. The as-prepared catalyst shows an obviously enhanced HER performance in alkaline media. Compared with pristine CoSe2, the overpotential of Sn doped catalyst with optimal doping content decreases from 189 mV to 117 mV at 10 mA cm −2 and the Tafel slope declines from 94 mV dec −1 to 86 mV dec −1, as well as shows long-term durability for 100 h. Experimental results and further density functional theory (DFT) calculations show that Sn doping can improve the ability of charge transfer and increase the electrochemical surface area, as well as optimize the hydrogen adsorption energy, all of which are instrumental in HER performance improvement. This work not only provides atomic-level insight into regulating the electronic structure of transition metal selenides by main group metal doping, but also broadens the avenue of developing high-efficiency and stable non-precious metal catalysts. Graphical abstract: Image 1 Highlights: Rational design and successful prepare the Sn–CoSe2 /CC electrode. The Sn–CoSe2 /CC exhibits greater enhanced HER performance compared with CoSe2 /CC. Sn doping can optimize the electronic structures and moderate ΔGH∗ of CoSe2 .